The Influence Of Health Education Using Video “SEMAR LARI” About Breast Examination On Knowledge, Attitude And Behavior In Adolescent Women - Anggita Dini Febriani; Nur Atiqoh; Retno Fitrianti Efendi; Yanik Muyassaroh (Journal of Midwifery Science: Basic and Applied Research, 2021)
Non-communicable diseases (NCDs) are one of the most common causes of death in Indonesia. The youth's understanding of BSE (Breast Self-Examination) is still low, so it needs health education through educative media. The existence of this study aims to increase knowledge, attitudes and behavior in young women with audiovisual media. SEMAR LARI (Semarak Perform Awareness) video is one of the efforts to make it easier for young women to understand the importance of BSE. The sample of this study amounted to 60 people who were divided into 2 groups. The first group used health education. The second second group uses audiovisual. The analysis was carried out by using the Mann Whitney test using the SPSS version 16 program. The value of p = 0.0001 or p 0.05 showed that there was an effect of counseling about BSE using video on knowledge, attitudes, and behavior in adolescent girls.  Key word: Video SEMAR LARI, BSE, Knowledge, Attitudes, Behavior